Why do onychophorans and camels need the same gestation time? - Monge-Nájera, Julián (2019)
One of the many mysteries surrounding onychophorans, is why, despite their small body size, they have gestation periods that are as long as gestation in some mammals. Here we propose that the causes are infrequent feeding and the Mandatory Minimum Size model, according to which they must be born sufficiently developed to hunt their own food and survive adverse microclimates.